2003
DOI: 10.1086/502149
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-Associated Pneumonia in a Multi-Hospital System Differences in Microbiology by Location

Abstract: Objective:To determine whether there were differences in the microbiologic etiologies of ventilator-associated pneumonia in different clinical settings.Design:Observational retrospective cohort study of microbiologic etiologies of ventilator-associated pneumonia from 1998 to 2001 in a multi-hospital system. Microbiologic results were compared between hospitals and between different intensive care units (ICUs) within hospitals.Setting:Three hospitals—one pediatric teaching hospital, one adult teaching hospital,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…The investigators used a cutoff value of 10 5 cfu/mL for differentiate between tracheobronchial colonization and infection. In contrast to these studies, a US study by Babcock et al 8 found that S. aureus (28.4% of isolates) was the predominant organism, followed by P. aeruginosa. It is believed that the differences in the etiologic agents of VAP found in different studies are the result of differences in the population of intensive care unit patients, duration of hospital stay, and prior antimicrobial therapy.…”
Section: Detection and Quantitation Of The Etiologic Agents Of Ventilmentioning
confidence: 83%
“…The investigators used a cutoff value of 10 5 cfu/mL for differentiate between tracheobronchial colonization and infection. In contrast to these studies, a US study by Babcock et al 8 found that S. aureus (28.4% of isolates) was the predominant organism, followed by P. aeruginosa. It is believed that the differences in the etiologic agents of VAP found in different studies are the result of differences in the population of intensive care unit patients, duration of hospital stay, and prior antimicrobial therapy.…”
Section: Detection and Quantitation Of The Etiologic Agents Of Ventilmentioning
confidence: 83%
“…A retrospective cohort study of the microbiologic etiology of VAP in the ICU setting was performed in three hospital settings: a large teaching hospital, a community hospital, and a children's hospital (5). The most commonly isolated organisms were similar across adult and pediatric hospitals: Staphylococcus aureus (28.4%), Pseudomonas aeruginosa (25.2%), and other gramnegative bacilli (26.6%).…”
Section: Microbiologymentioning
confidence: 99%
“…Pseudomonas aeruginosa is an important opportunistic pathogen responsible for nosocomial infections (2), burn infections (1,31), and chronic lung infections in cystic fibrosis (CF) patients (11). P. aeruginosa lung infections are difficult to eradicate in CF patients, even with intensive antibiotic treatment, probably due to the concurrent presence of multidrugresistant strains (5) and their biofilm mode of growth (11).…”
mentioning
confidence: 99%